ANALISIS KONTRASTIF IDIOM YANG MENGEKSPRESIKAN EMOSI DALAM BAHASA JEPANG DAN BAHASA INDONESIA - Sri Wahyu Istana Trahutami (Vocational College of Diponegoro University, 2023)
Abstract Prasetyo, Wisnu Aji. 2022. “Analisis Kontrastif Idiom yang Mengekspresikan Emosi dalam Bahasa Jepang dan Bahasa Indonesia”. Thesis. Japanese Language and Culture Undergraduate Study Program, Faculty of Humanities, Diponegoro University. Advisor: Sriwahyu Istana Trahutami, S.S., M.Hum.The research aims: 1. To describe the lexical and idiomatical meanings of Japanese and Indonesian idioms that express emotion; and 2. To describe the similarities and differences between Japanese and Indonesian idioms that express emotion. The research data were obtained from idiom dictionaries, online news sites, and online articles. The data collection method in this thesis was simak method with sadap and catat technique. Then, using contrastive analysis method to analysis the data. Meanwhile, informal method is used to presenting the results of the analysis. Based on the results of the analysis, it can be concluded that the similarities between Japanese and Indonesian idioms that express emotion are: 1. Both of these idioms are mostly dominated by expressions of anger; 2. Both of these idioms have similarities in idiomatical meanings; and 3. Both of these idioms has the meaning that comes out the most, namely the meaning of big anger. Meanwhile, the differences between Japanese and Indonesian idioms that express emotion are in Indonesian idioms there are no particles like in Japanese idioms. However, in Indonesian idioms there are additional prefixes, suffixes, and reduplications.Keywords: contrastive, idiom, emotion.